Analysis of drug compatibility in Y in intravenous therapy: preparation of a preventive tool for a university hospital in Petrolina - PE - Karina D. MORAES; Izabella V. GOMES; Odara P. LIMA; Raissa L. REIS; Marcilene N. SOUZA; Natalia D. FREIRE; Josilenne F. BARROS; Felipe S. MEDEIROS; Deuzilane M. NUNES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objectives: To elaborate instruments for the analysis of the compatibility of intrave-nous medications, in order to assist in the conduct and routines of the assistance teams of the Federal University of the São Francisco's Valley (HU-Univasf) Methods: Injectable drugs were initially selected, which belong to the HU-Univasf stand-ardization list. Information on the pH of medicines, compatibilities and incompatibili-ties, were extracted from the databases: Lexi-comp® Inc, Micromedex IV Compatibil-ity, Internet website Stabilis and King Guide to Parenteral Admixtures®. This work was carried out in two stages: (1) Creation of a tool to analyze the compatibility of injectable medications used in the hospital in a guide format; (2) Elaboration of the cross-table for quick consultation of the compatibility of the most prevalent medica-tions in the Intensive and Semi-Intensive Care Unit (UCISIN), in the parenteral dos-age form for intravenous administration (IV). Results: The Guide for analysis of Y compatibility in intravenous drug administration for a University Hospital in Petroli-na-Pe, was published with ISBN (International Standard Book Number): 978-85-92656-19-5 and it is available on the HU-Univas institutional website for free ac-cess. This material suited as the basis for the construction of the drug compatibility chart that contains the 50 most distributed items from the pharmacy to UCISIN. From this table, 1,225 pairs of drugs were obtained, of which 36% (N = 444) corresponded to compatible pairs and 20% (N = 241) to incompatible pairs. It should be noted that a higher value of pairs was observed with the indefinite compatibility 44% (N = 540), that is, without data in the consulted literature. Conclusions: It was possible to prepare the Guide for Analysis of Y Compatibility in Intravenous Medication Administra-tion and the HU-Univasf Y-Drug Incompatibility Cross-Table Graph, already availa-ble for the entire team. Therefore, it is expected that these instruments facilitate the access of the multiprofessional team to quality information, expanding the role of the pharmacist in the care of critical patients, improving patient safety in the use of intra-venous medications in the hospital.